Enhancing Sustainable Palm Oil Production in West Kalimantan: Paradiplomacy and Solidaridad's Role in Achieving Environmental Goals - Asiraf, Hafis; Haqqi, Halifa; Widhiyoga, Ganjar (Universitas Muhammadiyah Yogyakarta, 2023)
The global palm oil industry, particularly in West Kalimantan, Indonesia, faces significant environmental scrutiny, with deforestation for oil palm plantations adversely impacting its reputation. This challenge is compounded by the European Union's regulations against products causing environmental harm, pressuring regional governments to safeguard the sustainability of local agriculture. This study examines the West Kalimantan government's collaboration with Solidaridad Indonesia, a renowned educational and cooperative agency, in transforming the local palm oil industry towards sustainability. Employing a qualitative methodology with a focus on secondary data, the research explores West Kalimantan's paradiplomatic initiatives in the global market through its partnership with Solidaridad. This collaboration is analyzed through the lenses of paradiplomacy and sustainable development goals (SDGs). The findings reveal that West Kalimantan's paradiplomacy has significantly enhanced the image of its palm oil commodities. Key strategies include educational programs for local farmers, promotion of certified palm oil standards, and alignment with SDGs. The study highlights the success of this collaborative approach in meeting the aspirations of West Kalimantan's government towards sustainable development, offering a model for other regions facing similar environmental challenges in the palm oil sector.